New Data for Urn Burials of Guarani Archaeological Sites in the Southern Extreme of La Plata Basin - Mazza, Bárbara; Acosta, Alejandro; Loponte, Daniel (Revista Chilena de Antropología, 2017)
Many urn burials were recorded among the complex mortuary behaviors observed in archaeological sites belonging tothe Guaraní archaeological unit. Urn burial analyses are generally scarce and, particularly, in the southern point of La Plata basin. The objective of this work is to contribute to the Guaraní society’s knowledge by the analysis of human remains buried in urns from archaeological sites located in the Paraná Delta (Argentina). This region is the southern point of this Amazonian group’s expansion, whose mortuary remains are well preserved, in contrast to other Guarani´s regions. In this work, we analyze the human skeletal remains recovered from urn burials from three archaeological sites located in the Paraná Delta: Arroyo Malo, Arroyo Fredes y Arroyo La Glorieta. These sites were excavated at the beginning of the 20th century by many researchers and today are part of Museo de La Plata´s collections. We studied sexual composition, age and anatomical structure as well as a set of taphonomic variables. The results show the preponderance of male adult individuals, represented mainly by long bones and cranial elements, some of them with cut marks and red paint (ochre) in abundant quantities. These indicators, along with others of taphonomical origin, indicate the secondary treatment of the dead product of the disassembly, defleshing and selection of certain anatomical units.